Cu(II)@MXene based photothermal hydrogel with antioxidative and antibacterial properties for the infected wounds - Liu, Mingxiang; Zheng, Lei; Zha, Kangkang; Yang, Yayan; Hu, Yunping; Chen, Kai; Wang, Feng; Zhang, Kunyu; Liu, Wei; Mi, Bobin; Xiao, Xiufeng; Feng, Qian (Frontiers in Bioengineering and Biotechnology, 2023)
The regeneration of skin tissue is often impeded by bacterial infection seriously. At the same time, reactive oxygen species (ROS) are often overexpressed in infected skin wounds, causing persistent inflammation that further hinders the skin repair process.All of these make the treatment of infected wounds is still a great challenge in clinic.In this study, we fabricate Cu(II)@MXene photothermal complex based on electrostatic self-assembly between Cu2+ and MXene, which are then introduced into a hyaluronic acid (HA) hydrogel to form an antibacterial dressing. The rapid adhesion, self-healing, and injectability of the dressing allows the hydrogel to be easily applied to different wound shapes and to provide long-term wound protection. More importantly, this easily prepared Cu(II)@MXene complex can act as a photothermal antibacterial barrier, ROS scavenger and angiogenesis promoter simultaneously to accelerate the healing rate of infected wounds. Our in vivo experiments strongly proved that the inflammatory condition, collagen deposition, vessel formation, and the final wound closure area were all improved by the application of Cu(II)@MXene photothermal hydrogel dressing.